Analisis Peran Pemerintah terhadap Peningkatan Sertifikasi Halal UMKM di Kelurahan Teladan Barat Medan - Nurul Hikmah; Syamsul Effendi; Ismail Ismail (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
Halal icertification iis ione iform iof iassurance iof iproduct ihalalness ithat iis ivery iimportant ifor iMicro, iSmall, iand iMedium iEnterprises i(MSMEs), iespecially ithose iengaged iin ithe ifood iand ibeverage isector. iHalal icertification inot ionly iprovides icertainty iregarding ithe ihalal istatus iof ia iproduct ibut ialso iincreases iconsumer itrust iin ithe iproducts iproduced iby ibusiness iactors. iIn ithis icontext, ithe igovernment ihas ian iimportant irole iin iencouraging iand iassisting iMSMEs iin iobtaining ihalal icertification. iThis istudy iaims ito ianalyze ithe irole iof ithe igovernment iin iincreasing ihalal icertification ifor iMSMEs iin iTeladan iBarat iVillage, ito iidentify ithe iprograms ior iefforts icarried iout iby ithe igovernment iin isupporting ihalal icertification, iand ito idetermine ithe iresponse iof iMSME iactors ito ithe igovernment’s irole. This istudy iuses ia iqualitative iresearch imethod iwith ia idescriptive iapproach. iData icollection itechniques iwere icarried iout ithrough iinterviews, iobservations, iand idocumentation. iThe iinformants iin ithis istudy iconsisted iof iseveral iMSME iactors iin ithe ifood iand ibeverage isector iin iTeladan iBarat iVillage, iboth ithose iwho ialready ihave ihalal icertification iand ithose iwho ihave inot iyet iapplied ifor ihalal icertification. The iresults iof ithe istudy ishow ithat ithe igovernment ihas imade ivarious iefforts ito iincrease ihalal icertification iamong iMSME iactors ithrough isocialization iactivities, iproviding iinformation iregarding ithe iprocedures ifor iobtaining ihalal icertification, iand iassisting ibusiness iactors iin ithe iprocess iof iapplying ifor ihalal icertificates. iHowever, ithere iare istill iseveral iobstacles ifaced iby iMSME iactors, isuch ias ilimited iinformation, iperceptions iregarding ithe icomplexity iof iprocedures, iand ilimited itime ito imanage iadministrative irequirements. iTherefore, iincreased isocialization iand icontinuous iassistance iare ineeded iso ithat imore iMSME iactors iare iencouraged ito iobtain ihalal icertification ifor ithe iproducts ithey iproduce.